2020
DOI: 10.3390/metabo10050207
|View full text |Cite
|
Sign up to set email alerts
|

Systems Biology ARDS Research with a Focus on Metabolomics

Abstract: Acute respiratory distress syndrome (ARDS) is a clinical syndrome that inflicts a considerably heavy toll in terms of morbidity and mortality. While there are multitudes of conditions that can lead to ARDS, the vast majority of ARDS cases are caused by a relatively small number of diseases, especially sepsis and pneumonia. Currently, there is no clinically agreed upon reliable diagnostic test for ARDS, and the detection or diagnosis of ARDS is based on a constellation of laboratory and radiological tests in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 65 publications
(98 reference statements)
0
17
0
Order By: Relevance
“…We have found specific metabolic differences between ARDS patients induced by COVID-19 or IAP. Most of these metabolic alterations have been previously reported as biomarkers of ARDS or ARDS severity [ 8 10 ]. For example, a similar serum metabolic profile including proline, glutamate, phenylalanine, and valine was reported as a sensitive biomarker of ARDS severity (mild, moderate, and severe) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have found specific metabolic differences between ARDS patients induced by COVID-19 or IAP. Most of these metabolic alterations have been previously reported as biomarkers of ARDS or ARDS severity [ 8 10 ]. For example, a similar serum metabolic profile including proline, glutamate, phenylalanine, and valine was reported as a sensitive biomarker of ARDS severity (mild, moderate, and severe) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in amino acidic metabolism has been reported as one of the key features of ARDS development [ 8 , 9 ], and it has also been found significantly up-regulated in COVID-19 patients [ 34 , 39 , 46 , 47 ]. However, when we compared the metabolic profile of patients with ARDS due to COVID-19 or to IAP, we found that the amino acidic metabolism was decreased in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge metabolomics have not been used to study PARDS. Previous studies of adult ARDS ( Supplementary file 1 ) used targeted metabolomics platforms with relatively limited chemical space coverage ( Metwaly and Winston, 2020 ). Recently, Rogers et al used an untargeted metabolomics platform to compare the profile of pulmonary edema fluid collected at the time of endotracheal intubation for 16 adults with ARDS compared to 13 with cardiogenic pulmonary edema.…”
Section: Summary Of Research To Datementioning
confidence: 99%
“…Previously, ARDS groups have been studied in comparison to non-ARDS reference groups, such as healthy controls or hospitalized patients without ARDS [5][6][7][8][9][14][15][16]. Here, we present the first detailed comparative multi-omic analysis between COVID-19 ARDS (n=43) and bacterial sepsisinduced (non-COVID-19) ARDS (n=24).…”
Section: Introductionmentioning
confidence: 99%